Phase-selective doping of oriented regioregular poly(3-hexylthiophene-2,5-diyl) controls stability of thermoelectric properties - Guchait, Shubhradip; Dash, Aditya; Lemaire, Antoine; Herrmann, Laurent; Kemerink, Martijn; Brinkmann, Martin (Advanced functional materials, 2024)
This study focuses on the impact of dopant location in the semicrystalline structure of regioregular poly(3-hexylthiophene-2,5-diyl) on the long-term stability of thermoelectric properties probed in rub-aligned films. Phase-selective doping is possible by suitable choice of dopants. Anion exchange doping results in TFSI dopants located in both crystalline and amorphous domains whereas magic blue dopants are located in the amorphous phase only. The combination of rub-alignment, increasing concentration doping, and anion exchange doping is effective to produce doped P3HT films with enhanced thermoelectric properties and stability. Transmission electron microscopy, polarized optical absorption spectroscopy, and transport measurements help identify different regimes of doping: crystalline domains are doped first by exchange of F4TCNQ− with TFSI−, followed by a progressive doping of amorphous regions. The best thermoelectric performances of TFSI-exchanged P3HT lead to power factors in the 160-170 µW m−1 K−2 range. Despite similar TE performances, MB-doped and TFSI-exchanged P3HT films behave very differently on aging. Numerically exact kinetic Monte Carlo simulations clarify the origin of this difference. The retention of charges in any phase is crucial for the stability in conductivity, but the conductivity at long aging times, σ∞ is quantitatively determined by the specific phase retaining the charges.
Gesehen am 19.12.2024